Electricity Consumption and Information and Communication Technology (ICT) in the N-11 Emerging Economies - Afzal, Munshi Naser Ibne; Gow, Jeff (International Journal of Energy Economics and Policy, 2016)
In this study, the impact of information communication technologies (ICT) on electricity consumption in the Next 11 (N-11) emerging economies over the period 1990-2014 is examined. This period coincides with high economic growth rates in those countries and associated rapidly increasing electricity consumption as well as the ICT revolution that saw the rapid uptake of new ICT by its peoples. Little has been published on the relationship between ICT and electricity consumption in the N-11 emerging economies. This paper examines the hypothesis that increased use of ICT increases electricity consumption. Secondly, how different measures of ICT affect electricity consumption and finally, what are the short-run and long run elasticities of electricity demand with respect to ICT in N-11 countries? The methods used included dynamic panel data models (MG, PMG, system GMM) and show a positive and statistically significant relationship between ICT and electricity consumption where ICT is measured using internet connections, mobile phones or the import percentage of ICT goods of total imports. Long run ICT elasticities are smaller than income elasticities but because ICT growth rates are so much higher than economic growth rates, the impact of ICT on electricity consumption is greater than the impact of income on electricity consumption. Electricity demand projections in emerging economies, which do not include ICT as an explanatory variable, may underestimate actual electricity demand. This can lead to unplanned electricity shortages if actual electricity demand exceeds planned electricity demand. Thus, the paper gives policy recommendations based on the empirical results for the N-11 countries to address this problem. Keywords: N-11 countries, ICT, Electricity Consumption, Panel data, MGE, PMGE, system GMM JEL Classifications: L94, O1, N17, O10, Q43, J21